ANALISIS KOMPARASI KINERJA KEUANGAN ATAS IMPLEMENTASI KEBIJAKAN TAX AMNESTY (Studi Kasus pada PT. Bank Rakyat Indonesia (Persero), Tbk) - Retnani, Gitta Wahyu (Jurnal Ilmiah Mahasiswa FEB, 2017)
Tax amnesty is the government’s policy to stimulate state revenue from tax sector for accelerating national development. Tax amnesty funds, especially repatriation funds, are  submitted  by  the  third party  to  the  banks  appointed  as  perception  banks.  This research aims to compare the financial performance before and after the implementation of tax amnesty policy phase II and the repatriation fund projection, as well as to relate the  financial  performance and  earnings  by  the  end of  tax  amnesty  policy  phase  III implementation. The study is administered at PT. Bank Rakyat Indonesia (Persero) Tbk, one of the perception banks in Indonesia. The data are analyzed by means of Wilcoxon test toward the financial performance ratio calculation, which consist of LDR, NPL, CAR, ROA, BOPO and NIM. Besides, the projection is examined by least square trend, regression, and expected value analysis. The result of the study shows that bank financial performance has improved during the implementation of tax amnesty. When the estimated third party fund from repatriation to BRI can be obtained optimally and is likely to improve bank financial performance, the earnings can also be maximally gained.Keywords:  Tax  Amnesty,  Repatriation  Fund,  Third  Party  Fund, Bank  Financial Performance, Earnings.